1976
DOI: 10.1042/bj1580473
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal retention of a modified anti-inflammatory steroid

Abstract: In studies with synthetic lecithins, dipalmitoylphosphatidylcholine was found to be the preferred form for liposomal retention of cortisol esters at 37 degrees C. Cortisol palmitate was retained longer than cortisol octanoate, whereas unesterified cortisol escaped readily from liposomes. Such a liposome composition may allow the controlled release of modified anti-inflammatory agents, particularly when used for intra-articular administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Therefore, the effect of charge difference of these neutral liposomes DPBL and DPML, which is due to the positive charge of the Man-C4-Chol structure itself, on their uptake is excluded. Furthermore, the incorporated DP was stably retained in these liposomal formulations after a 48-h incubation correlated with a previous study involving the high retention of steroid palmitate in liposomes (Shaw et al, 1976, Teshima et al, 2004. These results confirm the stability of the liposomal formulations of DP for in vitro studies and intratracheal application in rats.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, the effect of charge difference of these neutral liposomes DPBL and DPML, which is due to the positive charge of the Man-C4-Chol structure itself, on their uptake is excluded. Furthermore, the incorporated DP was stably retained in these liposomal formulations after a 48-h incubation correlated with a previous study involving the high retention of steroid palmitate in liposomes (Shaw et al, 1976, Teshima et al, 2004. These results confirm the stability of the liposomal formulations of DP for in vitro studies and intratracheal application in rats.…”
Section: Discussionsupporting
confidence: 76%
“…There are several reports about the application of liposomes to incorporate dexamethasone (Dex), a potent GC, for lung inflammation by intratracheal (i.t.) administration (Tremblay et al, 1993;Suntres and Shek, 2000); however, difficulties in controlling the drug incorporation and retention in liposomes have been reported (Shaw et al, 1976). Benameur et al (1993) demonstrated that dexamethasone palmitate (DP), which is more lipophilic than Dex, was inserted in the lipid bilayer and showed significant encapsulation and retention in the liposomes.…”
Section: Inhalation Of Lipopolysaccharide (Lps)mentioning
confidence: 99%
“…Cortisol palmitate (CP) was obtained from ICI Pharmaceuticals Division, Macclesfield, Cheshire, UK. 3H-Cortisol palmitate was prepared according to the method of SHAW et al [10]. J4C-Cholesteryl oleate was obtained from New England Nuclear, Boston, Massachusetts.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, these effects are accompanied by serious dose-related toxic effects, which essentially restrict the use of steroids as anti-inflammatory agents to potentially life-threatening diseases, characterized by inflammation without infection. SHAW et al [10] have-shown that the palmitate ester of cortisol forms stable liposomes with dipalmitoyl phosphatidyl choline (DPPC). These liposomes were shown to have enhanced anti-inflammatory effects, compared to free cortisol, when injected directly into the knees of rabbits with an experimentally-induced arthritis [ 1 1].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, palmitate corticosteroid derivatives have also been studied since the late 1970s, with cortisol palmitate, prednisolone palmitate, and dexamethasone palmitate having been loaded into liposomes. [53][54][55] In our case, we loaded 5% molar concentration of PP into our liposomes with a In both cases (HRECs and HAECs) cells were exposed to free PH (25 lM) or PH loaded into either EPCR-targeting liposomes (EPCR-NL1), EPCR-targeting liposomes with PP in the membrane (EPCR-NL2), or nontargeting liposomes (P-NL1). The cells were subjected to the different treatments for 4 hours, then washed, and supernatants were collected 24 hours and 48 hour after the exposure.…”
Section: Discussionmentioning
confidence: 99%